Dyskeratosis congenita: natural history of the disease through the study of a cohort of patients diagnosed in childhood - Uria-Oficialdegui, M. L.; Navarro, S.; Murillo-Sanjuan, L.; Rodriguez-Vigil, C.; Benitez-Carbante, M. I.; Blazquez-Goñi, C.; Salinas, J. A.; Diaz-de-Heredia, C. (Frontiers in Pediatrics, 2023)
Background: Dyskeratosis congenita (DC) is a multisystem and ultra-rare hereditary disease characterized by somatic involvement, bone marrow failure, and predisposition to cancer. The main objective of this study is to describe the natural history of DC through a cohort of patients diagnosed in childhood and followed up for a long period of time.Material and methods: Multicenter, retrospective, longitudinal study conducted in patients followed up to 24 years since being diagnosed in childhood (between 1998-2020).: Fourteen patients were diagnosed with DC between the ages of 3 and 17 years (median, 8.5 years). They all had hematologic manifestations at diagnosis, and nine developed mucocutaneous manifestations during the first decade of life. Seven 3 presented severe DC variants. All developed non-hematologic manifestations during follow-up. Mutations were identified in 12 patients. Thirteen progressed to bone marrow failure at a median age of 8 years [range, 3-18 years], and eight received a hematopoietic stem cell transplant. Median follow-up time was 9 years [range, 2-24 years]. Six patients died, the median age was 13 years [range, 6-24 years]. As of November 2022, eight patients were still alive, with a median age of 18 years [range, 6-32 years]. None of them have developed myeloblastic syndrome or cancer. Conclusions: DC was associated with high morbidity and mortality in our series. Hematologic manifestations appeared early and consistently. Non-hematologic manifestations developed progressively. No patient developed cancer possibly due to their young age. Due to the complexity of the disease multidisciplinary follow-up and adequate transition to adult care are essential.